Konsep Pemberdayaan Masyarakat pada Penerapan Konstruksi Bangunan Pengolahan Batu Bata (Desa Kalase’rena Kecamatan Bontonompo Kabupaten Gowa) - Imriyanti -; Victor S.; Nasruddin -; Pratiwi M.; Hartawan -; Rasmi M.; Fitra AR. (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
Brick is a type of building material that functions as a wall. The processing of bricks requires land: a place to store the material, process, print, dry, burn, and store the bricks that have been burned and are ready to be marketed. The layout of the brick processing is not organized and the condition of the brick processing site (Bantilan) is very standard which uses makeshift construction. This activity aims to increase public awareness of the need for planning a building construction system for processing bricks to support the economy of the community. This stage of community empowerment involves the community directly in gathering information: identification of areas, needs, habits, and activities. The results of this community service show that the level of community understanding before the implementation of Bantilan construction 62% often experienced damage due to strong winds and material damage. A community empowerment level of 75% will participate in the process of implementing the Bantilan construction concept. The community satisfaction rate of 82% provides a sense of comfort and security in producing bricks. Community satisfaction with the construction concept of brick processing buildings, which is more efficient and effective as well as improving the economy of the brick processing community in the village of Kalase'rena.